Connecting children and families to nature: targeting wildlife agency education initiatives - Cohen, Christine E., author; Bruyere, Brett, advisor; Teel, Tara, committee member; Benson, Delwin, committee member (Colorado State University. Libraries, 2011)
The following thesis presents two manuscripts that explore how information on barriers to participation in nature-based programs and wildlife value orientations (WVOs) could be used to enhance the reach and effectiveness of wildlife agencies in connecting children to nature. Strengthened by proven physical, social and cognitive benefits as well as potential impacts upon the development of life-long environmental values and attitudes, wildlife agencies have an interest in addressing the human-nature disconnect in order to maintain and/or increase support for future conservation initiatives and secure future funding sources. The primary purpose of the first manuscript was to explore how information about WVOs, barriers to participation in nature-based programs and program topic preferences might be integrated to improve targeting of wildlife agency education initiatives for specific audiences. Data were collected via a mail survey administered to residents of Helena, Montana. Results indicated that there are significant differences in both barriers to participation and program topic preferences across WVOs. Although significantly different, limited barriers to participation were found for the relatively homogenous population surveyed indicating a need for further research to determine if findings can be applied to other populations and geographic locations. The second manuscript identified the specific program preferences and barriers for a group of teachers in Rapid City and Spearfish, South Dakota. A case study approach examined the barriers to both integrating EE into classrooms and incorporating programs taught by informal EE providers into curriculum. Focus group discussions provided valuable insight into how a local wildlife agency could most effectively target education efforts in order to overcome barriers and adapt programming for both students and teachers at a new education center in Rapid City, South Dakota. Results of focus group discussion provide recommendations for the design and marketing of school-based EE programs for Rapid City area teachers.
Keywords: environmental education; barriers to participation; education initiatives; program topic preferences; wildlife agencies; wildlife value orientations